The influence of sequential ligand exchange and elimination on the performance of P3HT:CdSe quantum dot hybrid solar cells. (29th October 2015) - Lee, Donggu; Lim, Jaehoon; Park, Myeongjin; Kim, Jun Young; Song, Jiyun; Kwak, Jeonghun; Lee, Seonghoon; Char, Kookheon; Lee, Changhee
Abstract: We report on a sequential ligand exchange and elimination process for the fast and easy surface modification of CdSe quantum dots (QDs) in order to improve the electronic interaction between poly(3-hexylthiophene) (P3HT) and CdSe QDs in P3HT:CdSe hybrid solar cells. We systematically investigated the influence of surface treatment on the insulating ligand shell of CdSe QDs using 1 H-NMR analysis, and correlated their influence on the photovoltaic properties of P3HT:CdSe hybrid solar cells. A decrease in the average thickness of the ligand shells directly improved carrier transport properties. Moreover, the presence of remnant 1-hexylamine ligands provided efficient surface trap passivation. As a result, overall solar cell performance (especially fill factor and power conversion efficiency) was enhanced and the recombination mechanism was dominated by monomolecular recombination due to enhanced carrier collection length ( l C0 ).